2007
DOI: 10.1016/j.pubrev.2006.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Blog power: Examining the effects of practitioner blog use on power in public relations

Abstract: While blogs are not yet a standard public relations tool, practitioners use blogs to enhance their power within their organizations. Using an online survey of public relations practitioners, this pilot test examined the relationship between power and blog use. Three factored categorizations of blog use among practitioners emerged: routine information and research, interactive blog communication, and issues identification. Results showed differences based on power, between blog users and non-users, owner-practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 12 publications
3
38
0
2
Order By: Relevance
“…Digital communication has been linked to managerial roles for public relations and previous research found that practitioners who used social networking sites and social media tools were more likely to report feeling empowered to their current position, have greater perceived expertise, and feel greater prestige within their organizations (Diga & Kelleher, 2009;Porter et al, 2007;Porter & Sallot, 2005;Sallot et al, 2004).…”
Section: Macro-level Approachmentioning
confidence: 99%
“…Digital communication has been linked to managerial roles for public relations and previous research found that practitioners who used social networking sites and social media tools were more likely to report feeling empowered to their current position, have greater perceived expertise, and feel greater prestige within their organizations (Diga & Kelleher, 2009;Porter et al, 2007;Porter & Sallot, 2005;Sallot et al, 2004).…”
Section: Macro-level Approachmentioning
confidence: 99%
“…Broader publications have considered the influence of blog(ger)s on politics and mass communications (e.g. Porter et al, 2007), tourism (e.g. Lin and Huang, 2006), journalism (e.g.…”
Section: Csr Communications and Bloggingmentioning
confidence: 99%
“…Public relations practitioners have described blogs as a tool that can influence individuals and publics (Kent, 2008). Porter, Sweetser Trammell, Chung, and Kim (2007) found practitioners who used blogs felt they had more power in the sense of expertise and prestige than those who were not blogging. Kent (2008) said the single greatest strength of blogs and the most important trait to public relations practitioners is the ability for publics to participate in the framing of online news and other information.…”
Section: Researchmentioning
confidence: 99%
“…Although most of the organizations did not follow a set schedule for blog post topics, they all emphasized the need to keep the information current and frequent. Using a set schedule for blog posting represents the organization's attempt to create relationships and maintain existing relationships based on consistency and accountability (Kelleher, 2008;Porter et al, 2007). The participants said their organizations focused their blog posts and other content matter to the subject of the commodity or other information that impacts the organization.…”
Section: Conclusion/implications/recommendationsmentioning
confidence: 99%